BEBERAPA MODEL, PENDEKATAN, STRATEGI, DAN METODE DALAM PEMBELAJARAN MATEMATIKA - Erita, Selvia (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2016)
This paper deals with some models, approaches, strategies and methods in the study of mathematics. Issues discussed were the definition, characteristics and types of model, approach, strategy and methods in the study of mathematics. How to choose and define models, approaches, methods and learning strategies. Teachers efforts in organizing and using a variety of teaching variables is an important part in the success of students achieve the planned objectives. Therefore, the selection of methods, strategies and approaches in a classroom situation in question is very important. The effort to develop teaching strategies grounded in the understanding that teaching is a form of efforts to give guidance to students for learning activities or in other words membelajarkan students as mentioned above. From here reflected an understanding that learning is not solely result oriented, but also process-oriented. The quality of the process will provide a space in determining the quality of the results achieved.